Assessment of Knowledge, Perception, Experience, and Phobia Toward Corticosteroids Among the General Public in Two Southeast Asian Countries - Muna Barakat PhD; Shaymaa B. Abdulrazzaq MSc; Lujain F. Alzaghari MSc; Diana Ramatillah PhD; Raihan Fadhil Muhammad BSc; Mohamed Hassan Elnaem PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
The widespread use of corticosteroids, particularly during the COVID-19 pandemic, has emphasized their therapeutic benefits while also raising public concerns regarding their safety and side effects. This study aims to assess the public’s knowledge, perceptions, experiences, and corticophobia related to corticosteroid use in Indonesia and Malaysia. A cross-sectional study was conducted using a pre-validated online questionnaire distributed to the general public. Descriptive statistics, knowledge and corticophobia score computations, and linear regression analysis were performed to analyze the data. A total of 553 participants were included in the study, with a majority being female (n = 403, 72.9%) and a median age of 22 ± 5 years. The results revealed inadequate knowledge among participants, with a median score of 7 (interquartile range [IQR] ± 4) out of 14. The corticophobia score was moderate, with a median of 3 (IQR ± 1.8) out of 5. Age demonstrated a significant positive association with knowledge (β = .141, P  = .022). Additionally, individuals from the health sector exhibited significantly higher knowledge and lower corticophobia compared to those from non-health sectors (β = −.427, P  < .001). This study identified significant knowledge gaps and moderate levels of corticophobia regarding corticosteroid use in Malaysia and Indonesia. These findings underscore the need for enhanced public education and targeted healthcare interventions to address misconceptions and improve awareness of corticosteroids.